2009
DOI: 10.1111/j.1472-765x.2009.02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of quorum-sensing inhibitor-like compounds from bacteria isolated from the brown algaColpomenia sinuosa

Abstract: Aims:  Several Gram‐negative bacterial species use N‐acyl homoserine lactone (AHL) molecules as quorum‐sensing (QS) signals to regulate various biological functions. Similarly, various bacteria can stimulate, inhibit or inactivate QS signals in other bacteria by producing molecules called as quorum‐sensing inhibitors (QSI). Our aim was to screen and identify the epibiotic bacteria associated with brown algae for their ability of producing QS‐inhibiting activity. Methods and Results:  QSI screenings were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Also, S. liquefaciens, S. plymuthica, and S. rubidaea were associated with the rhizosphere of oilseed rape, and all three demonstrated antifungal properties (208). In addition, S. rubidaea was found associated with marine alga in one study (209).…”
Section: Natural Distribution Of Serratia Speciesmentioning
confidence: 98%
“…Also, S. liquefaciens, S. plymuthica, and S. rubidaea were associated with the rhizosphere of oilseed rape, and all three demonstrated antifungal properties (208). In addition, S. rubidaea was found associated with marine alga in one study (209).…”
Section: Natural Distribution Of Serratia Speciesmentioning
confidence: 98%
“…In addition to the furanones of D. pulchra, a variety of bacteria and eukaryotes have been shown to produce cyclic dipeptides that can act as AHL mimics and affect QS-regulated behavior in other bacteria (Dobretsov et al 2009;Dickschat 2010). Recently, Kanagasabhapathy et al (2009) suggested that certain epibiotic bacteria from the brown macroalga Colpomenia sinuosa may play a role in defense mechanisms and suppress the settlement of other competitive bacteria by producing quorum sensing inhibitors (QSI) or QSI-like compounds.…”
Section: "Me´nages A`trois" Quorum Sensing Mediated Bacterial-macroamentioning
confidence: 98%
“…During the past decade it has been shown that various macroalgae are able to stimulate, inhibit, or inactivate QS signals in bacteria by producing QS inhibitors or analogs thereof (Maximilien et al 1998;Joint et al 2007;Kanagasabhapathy et al 2009). The Australian red macroalga Delisea pulchra produces halogenated furanones, structural analogs to N-acyl homoserine lactones.…”
Section: "Me´nages A`trois" Quorum Sensing Mediated Bacterial-macroamentioning
confidence: 99%
“…Aquatic ecosystems continue to reveal diverse microorganism taxonomies and to yield enormous diversity in secondary metabolite products. Numerous reports are emerging that provide empirical data demonstrating QSI activity from various marine sources that include sponges (290), microalgae (291), bryozoa (292), and alga-and coral-associated bacteria (293,294). Low-micromolar concentrations of phenethylamide compounds from the marine bacterium Halobacillus salinus were found to inhibit V. harveyi luminescence and C. violaceum pigment production without inhibiting growth (295).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%